1980
DOI: 10.1002/art.1780231204
|View full text |Cite
|
Sign up to set email alerts
|

Efefct of long‐term treatment with circulating thymic factor on murine lupus

Abstract: Mice from three different strains (NZB, B/W, and Swan) which spontaneously develop a lupus-like disease and show a premature decline of their secretion of the circulating thymic factor, Facteur Thymique Serique (FTS), were treated repeatedly with FTS and followed for the evolution of their autoimmune disease. The autoimmune sialoadenoitis (Sjogren's syndrome) appearing in NZB and B/W mice, evaluated here by a scintigraphic method, was completely prevented or even cured by FTS treatment. T h e increase in antie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Furthermore, the increase in anti-erythrocyte autoantibody production was transiently delayed in aged NZB mice. Conversely, anti-DNA antibody production either remained unaffected or was accelerated (in B/W mice) by FTS treatment, demonstrating that the restoration of the failing thymic secretion does influence autoantibody production, in a manner depending primarily on the auto-antigen eliciting the autoimmune response [6].…”
Section: Animal Models For Rheumatoid Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the increase in anti-erythrocyte autoantibody production was transiently delayed in aged NZB mice. Conversely, anti-DNA antibody production either remained unaffected or was accelerated (in B/W mice) by FTS treatment, demonstrating that the restoration of the failing thymic secretion does influence autoantibody production, in a manner depending primarily on the auto-antigen eliciting the autoimmune response [6].…”
Section: Animal Models For Rheumatoid Arthritismentioning
confidence: 99%
“…Moreover, in thymectomized mice, FTS restored colony-forming unit by entry into DNA synthesis after T-dependent antigen treatment [31,36]. Restoration of the failing thymic secretion did influence auto-antibody production, in a manner depending primarily on the auto-antigen eliciting the autoimmune response [6,9,82]. In addition, administration of sodium diethyldithiocarbamate (a chelating agent used primarily in the analytical determination of copper, arsenic, nickel and other metals) gave evidence for a role of the thymus, and its hormones, in the control and regulation of factors inducing thymocyte differentiation [52,74].…”
Section: Role In Neuro-immune-endocrine Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the resistance of NZB mice to tolerance induction by heterologous gamma globulins was found to be assigned to a T cell defect [12] that occurred independently of B cell abnormalities [19]. Moreover, thymus grafts and thymic factors were shown to modulate NZB mouse humoral immune responses directed against autoantigens [20,211 or foreign antigens [22] and recent data indicated that in normal mouse strains, an autoimmune disease could be more easily induced by polyclonal B cell activators in thymectomized than in intact animals [23].…”
Section: S0 Hgpital Necker Parismentioning
confidence: 99%